Community Empowerment Through Financial Management Training and Business Development of The Borobudur Homestay in Candirejo Village, Magelang District - Dapit Pamungkas , Imang; Hapsari, Dian Indriana; Rahayu , Emik; Ahmad Asshofi , Izza Ulumuddin; Aldo Irawan , Joseph; Ramdhani , Aji Kusumah Ramdhani; Widyatmoko , Karis; Wahyu Mulyono , Ibnu Utomo; Nurjanah, Nurjanah (Universitas Ahmad Dahlan, 2023)
Background: Community-based tourism is increasingly being considered a more sustainable alternative. Tourism Villages can be a step towards realizing sustainable tourism. This is because the tourism village has the opportunity to open up as much participation as possible for the local community. However, this does not mean anything if managers, including accommodation providers, need qualified organizational and financial management skills. Contribution: This activity aims to provide knowledge to homestay managers in Candirejo Village to properly manage business finances based on SAK EMKM (Standar Akuntansi Keuangan Entitas Mikro, Kecil, dan Menengah) Method: The method used by researchers is through training and empowerment of homestay managers Results: The result of this activity is an increased understanding of SAK EMKM in Candirejo Village. After the training, homestay managers have also started implementing SAK EMKM in their financial reports. As a result, the financial position can be monitored, financial leaks can be minimized, and homestay business management can be carried out more effectively and efficiently. Conclusion: The activities that were held went well. This is known from the excellent understanding of SAK EMKM after the training was given